2018
DOI: 10.1007/s13300-017-0356-2
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c is Positively Associated with Serum Carcinoembryonic Antigen (CEA) in Patients with Diabetes: A Cross-Sectional Study

Abstract: IntroductionTo explore the influence of glycemic levels on the serum carcinoembryonic antigen (CEA) levels in patients with diabetes.MethodsThis is a cross-sectional study. Patients with diabetes aged 18–75 years old were recruited. Those patients with carcinoma, abnormal renal function (serum creatinine ≥ 115 μmol/l), and abnormal hepatic function (serum alanine aminotransferase ≥ 97.5 U/l) were excluded in this study. Blood samples were obtained from every patient after an overnight fasting, and CEA was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
(27 reference statements)
2
18
0
Order By: Relevance
“…BMI negatively affected CEA levels in only the diabetes group, not in the normal or prediabetes subgroup. Similar to our study, Lu et al reported that male diabetic patients had higher CEA levels than females, and obese diabetic patients had lower CEA levels than patients with a normal BMI . We demonstrated that HbA1c is an independent factor that influences the level of CEA in subjects of both sexes with diabetes.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…BMI negatively affected CEA levels in only the diabetes group, not in the normal or prediabetes subgroup. Similar to our study, Lu et al reported that male diabetic patients had higher CEA levels than females, and obese diabetic patients had lower CEA levels than patients with a normal BMI . We demonstrated that HbA1c is an independent factor that influences the level of CEA in subjects of both sexes with diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…We demonstrated that HbA1c is an independent factor that influences the level of CEA in subjects of both sexes with diabetes. Since we reviewed the medical records thoroughly and excluded other clinical conditions that might affect CEA levels, including smoking, the β value was significantly higher than that reported previously by Lu et al…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations